Professional financial and accounting services in the light of European Union directives and the deregulation of professions in Poland – current status and research needs - Ciechan-Kujawa, Marlena (Copernican Journal of Finance & Accounting, 2015)
The article describes the issue of the impact of legislative changes on the market of professional accounting and financial services. It discusses the scope and essence of the changes both to the directives of the European Union and the deregulation of the profession of the accounting and finance in Poland. This article contains findings regarding the experience of European countries and presents the selected research results. In conclusion, the author indicates and justifies direction in research, which is essential to identify the determinants of the functioning and development of professional finance and accounting services in Polish economic practice after the legislative changes as well as the mechanisms of their impact on the risks (opportunities and threats) for sustainable development of entities and security of business trading.